(untitled) (Research, Society and Development, 2022)
Purpose: to characterize the sociodemographic profile of the team at a hospital FNU, to verify the level of knowledge of the team in relation to the topics of safety and correct patient identification, and to diagnose the process of patient identification and diet distribution. Methods: this is a study with a qualitative-quantitative, descriptive and cross-sectional approach, carried out in a UAN of a public hospital in the city of Aracaju, Sergipe, Brazil. They were part of the research but were submitted to a semi-structured questionnaire regarding knowledge related to the themes of Patient Safety and Correct Patient Identification. The situational diagnosis was carried out by observing the identification tags and diet trays served in the main meals, producing any identified failures. The occurrence of near misses was quantified by the Diet Near Error Index (IQE). Results: most participants answered knowing the definition of patient safety, however, only 53.3% made an association between the term patient safety and correct identification. The IQE identified was 39.3%. Conclusion: this study showed the level of knowledge of the functions regarding the topic addressed and that they did not use the guidelines in their work routine, indicating the need for training that addresses the topic beyond the notions of good food handling practices. Periodic qualifications are also indicated for maintenance and consolidation of acquired knowledge.